Dual-wavelength thulium-doped fiber laser assisted by non-adiabatic tapered fiber - Al-Alimi, Abdulmoghni Ali Wazea; Abu Bakar, Muhammad Hafiz; Zainol Abidin, Nadiah; Abas, A. F.; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (Elsevier, 2019)
MUHAMMAD HAFIZ BIN ABU BAKAR/// NADIAH HUSSEINI BINTI ZAINOL ABIDIN,MOHD ADZIR BIN MAHDI/// Al-Alimi, A.W,Abas, A.F,Alresheedi, M.T.